Belalang Kembar Siam Berkepala Dua sebagai Inspirasi Desain Busana Kostum untuk Perempuan - Purnama, Cecilia Agata; Aryani, Dewi Isma; Tan, Indra Janty (Telkom University, 2023)
The extremely rare occurrence of conjoined twins in grasshoppers served as the inspiraton for the POLYCHYPERA collecton. Photographer Juan Camarillo from South America saw this two-headed grasshopper and utlized it as a photo subject for the image ttled “Two Headed Grasshopper.” By exhibitng one head’s conditon on the front-back and top-down sides of each outit, the grasshopper’s singularity serves as a source of inspiraton for the design of costume apparel. The POLYCHYPERA costume collecton is created with the contrast impact in mind. Finding a distnctve costume design development concept using an anthropomorphic approach is how the study challenge is stated. This study aims to develop a concept and product design for dramatc-styled costume garments. By experimentaton and reading, the research method employs the project-based learning approach. The fndings of this study are antcipated to serve as a guide for comparable fashion designs that can develop the innovatve creatvity of fashion industry players.